Novel methods for the analysis of toxicants in bronchoalveolar lavage fluid samples from e‐cigarette, or vaping, product use associated lung injury (EVALI) cases: Terpenes. (13th August 2020) - De Jesús, Víctor R.; Silva, Lalith K.; Newman, Cody A.; Blount, Benjamin C.
Abstract : Rationale: Over 2800 e‐cigarette, or vaping, product use‐associated lung injury (EVALI) cases were reported to the Centers for Disease Control and Prevention (CDC) during August 2019 to February 2020. Bronchoalveolar lavage (BAL) fluid samples from 51 EVALI and 99 non‐EVALI cases were analyzed for toxicants including terpenes. We describe a novel method to measure selected terpenes in BAL fluid by gas chromatography/tandem mass spectrometry (GC/MS/MS). Methods: α‐Pinene, β‐pinene, β‐myrcene, 3‐carene, and limonene were measured in BAL fluid specimens by headspace solid‐phase microextraction/gas chromatography/tandem mass spectrometry. We created and characterized BAL fluid pools from non‐EVALI individuals to determine assay accuracy, precision, linearity, limits of detection, and analytical specificity. All measurements were conducted in accordance with the CDC's Division of Laboratory Sciences rigorous method validation procedures. Results: Matrix validation experiments showed that calibration curves in BAL fluid and saline had similar slopes, with differences of less than 7%. The assay precision ranged from 2.52% to 5.30%. In addition, the limits of detection for the five analytes ranged from 1.80 to 16.8 ng/L, and the linearity was confirmed with R 2 values >0.99. Conclusions: We developed and validated a method to quantify selected terpenes in BAL fluid specimens using GC/MS/MS. The assay provided accurate and precise analyses of EVALI and non‐EVALI BAL fluid specimens in support of CDC's EVALI response. This method is applicable to the determination of a broad range of terpenes in BAL fluid specimens.